2014
DOI: 10.1111/sltb.12131
|View full text |Cite
|
Sign up to set email alerts
|

Who Leaves Suicide Notes? A Six‐Year Population‐Based Study

Abstract: Popular culture insists on the significance of suicide notes, but research has yielded conflicting results about who leaves notes. Utilizing 6 years of suicides from a comprehensive statewide data surveillance system, differences were examined between cases with suicide notes and those without in terms of demographics, circumstances of the suicide, and precipitating circumstances. Of the 2,936 suicides, 18.25% included a note. Demographics and circumstances did not differ for cases with a note compared to case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 18 publications
0
22
4
2
Order By: Relevance
“…To date, the literature comparing suicide decedents who do and do not leave a note has reported conflicting findings with the prevalence of suicide note-leaving varying considerably across cultures, ethnicities, race, age, gender, socioeconomic status, and literacy. Of those who died by suicide, 15%-61% left a suicide note (Carpenter et al, 2016;Cerel et al, 2015;Meyer et al, 2017;O'Donnell et al, 1993;Salib et al, 2002). While Carpenter et al (2016) reported the highest rate of note-leaving, they have broadened the definition of suicide note to include verbal threats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, the literature comparing suicide decedents who do and do not leave a note has reported conflicting findings with the prevalence of suicide note-leaving varying considerably across cultures, ethnicities, race, age, gender, socioeconomic status, and literacy. Of those who died by suicide, 15%-61% left a suicide note (Carpenter et al, 2016;Cerel et al, 2015;Meyer et al, 2017;O'Donnell et al, 1993;Salib et al, 2002). While Carpenter et al (2016) reported the highest rate of note-leaving, they have broadened the definition of suicide note to include verbal threats.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that included in their analyses psychiatric histories and psychiatric hospitalizations reported contradictory findings. Several international studies reported that suicide decedents who had known mental health issues such as mental disorder, history of self-harm, or recent or prior psychiatric hospitalization were less likely to leave behind a note (Carpenter et al, 2016;Chia, Chia, & Tai, 2008;Demirel, Akar, Sayin, Candansayar, & Leenaars, 2008;Ho et al, 1998;Howard & Surtees, 2016;Kuwabara et al, 2006;Paraschakis et al, 2012;Salib et al, 2002;Wong, Yeung, Chan, Yip, & Tang, 2009). Stack and Rockett (2016), in their analysis of US data from the National Violent Death Reporting System, found that those with current mental health issues or depression were more likely to have left a suicide note (OR = 1.11 & OR = 1.22, respectively); however, those with current mental health treatment and alcohol abuse-related problems (15% and 24%, respectively) were less likely to have left a note.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Por lo que respecta a las notas suicidas, los resultados son muy semejantes a los encontrados en muestras gallegas 37 y norteamericanas 38 . En todos los casos un 18% de las personas que se suicidaron dejaron una nota suicida.…”
Section: Discussionunclassified